Size-dependent mechanical performance and defect sensitivity in T4,4,4-graphyne nanosheets: A comprehensive multi-parameter investigation - Yanping Fu; Linlin Zhang; Jie Zhang (PLoS ONE, 2026)
The mechanical performance of T4,4,4-graphyne was systematically investigated using molecular dynamics (MD) simulations. The study explores the effects of structural size, temperature, defect density, and layer count on key mechanical properties, including elastic modulus, ultimate tensile strength, and toughness. Results reveal a significant size-dependent enhancement in mechanical properties, with increasing nanosheet length leading to higher stiffness, strength, and energy absorption capacity. Conversely, elevated temperatures cause a notable degradation in these properties due to thermal softening and bond weakening. The presence of randomly dispersed vacancy defects severely compromises the material’s mechanical integrity, with even low defect concentrations causing substantial reductions in modulus, strength, and toughness. Additionally, multilayer configurations exhibit improved mechanical behavior compared to monolayers, attributed to enhanced interlayer load transfer and reduced surface effects. The fracture process, analyzed under uniaxial tension, shows brittle failure characteristics with anisotropic crack propagation behavior, consistent with the directional bonding in T4,4,4-graphyne. These findings provide critical insights into the mechanical response of this emerging 2D material, offering valuable guidance for its application in nanoelectromechanical systems, flexible electronics, and high-strength composite materials.